2023
DOI: 10.1248/cpb.c23-00387
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Novel Triaryl Derivatives with Readthrough-Inducing Activity

Shota Kawai,
Shunsuke Takashima,
Masafumi Ando
et al.

Abstract: The readthrough mechanism, which skips the premature termination codon and restores the biosynthesis of the defective enzyme, is an emerging therapeutic tactic for nonsense mutation-related diseases, such as Hurler syndrome, a type of mucopolysaccharidosis. In the present study, novel triaryl derivatives were synthesized and their readthrough-inducing activities were evaluated by a luciferase reporter assay with a partial α-L-iduronidase (IDUA) DNA sequence containing the Q70X nonsense mutation found in Hurler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…KY-516 was effective against the Q70X nonsense mutation, but less effective against the W402X nonsense mutation. 11) In addition, KY-516 was ineffective even at 30 µM in the Hurler patient-derived fibroblasts carrying the W402X mutation used in this study. Therefore, we investigated the sequence specificity of the readthrough-inducing activity of KY-640 using the previously reported luciferase assay system.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…KY-516 was effective against the Q70X nonsense mutation, but less effective against the W402X nonsense mutation. 11) In addition, KY-516 was ineffective even at 30 µM in the Hurler patient-derived fibroblasts carrying the W402X mutation used in this study. Therefore, we investigated the sequence specificity of the readthrough-inducing activity of KY-640 using the previously reported luciferase assay system.…”
Section: Resultsmentioning
confidence: 76%
“…Therefore, we investigated the sequence specificity of the readthrough-inducing activity of KY-640 using the previously reported luciferase assay system. 11) The results obtained showed that the readthroughinducing activity of KY-640 was stronger against the W402X mutation than the Q70X mutation (data not shown), in contrast to that of KY-516. The reason for the difference in sequence specificities between KY-516 and KY-640 remains unknown; however, each of the previously reported readthrough-inducing compounds was previously shown to have different sequence specificities, which may also be affected by the peripheral sequence of a nonsense mutation.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations